Real-life treatment of metastatic colorectal cancer with regorafenib: a single-centre review - Gotfrit, J. (Curr Oncol, 2017)
BACKGROUND: Various tyrosine kinase signalling pathways affect the development and progression of colorectal cancer (crc). In clinical trials, regorafenib has been associated with a survival benefit in metastatic crc (mcrc). We assessed the safety and efficacy of regorafenib in real-world patients. METHODS: In a retrospective review of patients with mcrc treated with regorafenib at our institution from 2013 to 2015, patient demographics, treatment, and survival data were collected. Progression-free survival (pfs) and overall survival (os) were estimated using the Kaplan–Meier method. RESULTS: In total, 48 patients were offered regorafenib, and 35 (73%) started treatment. Of the patients who started regorafenib, 57% were men. Median age in the cohort was 61 years, and all patients had a performance status in the range 0–2. Time from diagnosis of mcrc to regorafenib treatment was more than 18 months in 71% of patients. Starting dose was 160 mg in 54% of the patients, 120 mg in 40%, and 80 mg in 6%. Dose reductions occurred in 34% of the patients, and interruptions, in 29%. Best response was progressive disease (60%) and stable disease (17%); response in the rest of the patients was unknown. The most common adverse events on regorafenib (any grade) were fatigue (57%), hyperbilirubinemia (43%), thrombocytopenia (37%), anorexia (31%), and hypertension (31%). The most common grade 3 or 4 adverse events were fatigue (29%), hypophosphatemia (17%), weight loss (11%), and hyperbilirubinemia (9%). Common reasons for discontinuing regorafenib included progressive disease (51%) and toxicity (26%). In patients treated with regorafenib, pfs was 2.4 months (95% confidence interval: 1.8 to 3.3 months) and os was 5.6 months (95% confidence interval: 3.7 to 8.9 months). No factors were associated with survival in univariate or multivariate analysis. CONCLUSIONS: In a real-world setting, regorafenib is associated with survival similar to that reported in the randomized controlled trials, but at the expense of toxicity leading to discontinuation in many patients. Future studies of regorafenib should focus on identifying the patients most likely to benefit and on minimizing toxicity.